2018
DOI: 10.1109/tps.2018.2820387
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Helical Flux Compression Generator

Abstract: Electronic Structure of Superconducting Ta 4Pd3Te16. -The electronic structure of Ta 4Pd3Te16 is analyzed by tight-binding band calculations based on the extended Hueckel method. The compound electronically shows a quasi 1D behavior even though it possesses a layered structure. A strong orbital interaction is found only along the crystallographic b-direction. Fermi surface nesting disappears in Ta 4Pd3Te16 due to the weak interaction between Ta-Te and Pd-Te polyhedra. The compound is discussed to be a potentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Using the simulation approach described in [7], we will demonstrate that HFCG with double-end initiation makes it possible to generate pulses with faster rise time and higher power delivered to the inductive load than HFCG with single-end initiation, when designed in the same dimensions. In conclusion, it will be shown that HFCG with half-and-half stator and double-end initiation makes it possible to increase significantly the amplitude of the current switched by an electro-explosive opening switch (EEOS).…”
Section: Introductionmentioning
confidence: 99%
“…Using the simulation approach described in [7], we will demonstrate that HFCG with double-end initiation makes it possible to generate pulses with faster rise time and higher power delivered to the inductive load than HFCG with single-end initiation, when designed in the same dimensions. In conclusion, it will be shown that HFCG with half-and-half stator and double-end initiation makes it possible to increase significantly the amplitude of the current switched by an electro-explosive opening switch (EEOS).…”
Section: Introductionmentioning
confidence: 99%
“…Using the simulation approach described in [7], we will demonstrate that HFCG with doubleend initiation makes it possible to generate pulses with faster rise time and higher power delivered to the inductive load than HFCG with single-end initiation, when designed in the same dimensions. In conclusion, it will be shown that HFCG with half-and-half stator and double-end initiation makes it possible to increase significantly the amplitude of the current switched by an electro-explosive opening switch (EEOS).…”
Section: Introductionmentioning
confidence: 99%